A single-center’s uric acid profile in girls with Turner syndrome - Guo, Song; Chen, Qiuli; Zhang, Jun; Wei, Meihua; Zheng, Rujiang; Wang, Bing; Li, Yanhong; Ma, Huamei; Jiang, Xiaoyun (Frontiers in Endocrinology, 2024)
Background Metabolic disorders are common in individuals with Turner syndrome (TS). Hyperuricemia is associated with metabolic syndrome. This study investigated the serum uric acid (SUA) profile in patients with TS. Methods A retrospective observational study was conducted with 145 patients with TS. A total of 72 normal girls were in the control group from 2015 to 2024: 86 TS patients were treated with growth hormone (GH), 80 with stanozolol, and 52 with estrogen. Results Hyperuricemia was present in 33.1% (47/145) of patients with untreated TS and in 16.67% (12/72) of the controls (P < 0.001). Multivariable linear regression analysis showed that BMISDS, fasting serum glucose, and eGFR explained 34.4% (model R2 = 0.344) of the total variation in SUA in the untreated TS group. SUA and SUASDS (SUA standard deviation score) levels generally showed a slow rising tendency with age. SUA increased significantly in the first year of stanozolol initiation (P = 0.032), while adding estrogen and stanozolol improved the lipid profile during the whole assessment period. Conclusion Girls with TS showed a slow rising tendency in SUA and SUASDS with age and had higher SUA and SUASDS levels and incidence of hyperuricemia compared to their healthy female peers. The independent risk factors for hyperuricemia in pediatric patients with TS were BMISDS, HOMA-IR, glucose, and eGFR. The incidence of hyperuricemia increased in the first year of stanozolol treatment.